1984
DOI: 10.1123/jsp.6.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes During Self-Paced Motor Performance: An Electroencephalographic Profile of Skilled Marksmen

Abstract: In the initial phase of the study (Study 1) electrocortical arousal (EEG alpha activity) was assessed at four standardized sites (T3, T4, 01, and 02) from male and female (N = 17) international-caliber marksmen during rifle shooting performance. The task consisted of the execution of 40 shots at a conventional indoor target from the standing position. During each shot preparation, a significant increase in left temporal and occipital alpha activity was demonstrated, while the right hemispheric activity remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 16 publications
15
135
0
2
Order By: Relevance
“…Previous studies have revealed that successful rifle and pistol shooting performance is associated with increasing alpha-band (8 -13 Hz) power at certain sites across the cortex, especially the left anterior temporal cortex (e.g. Hatfield, Landers, & Ray, 1984). In contrast, poor shots have been associated with event-related desynchronization (e.g.…”
Section: Electroencephalography and Observationmentioning
confidence: 97%
“…Previous studies have revealed that successful rifle and pistol shooting performance is associated with increasing alpha-band (8 -13 Hz) power at certain sites across the cortex, especially the left anterior temporal cortex (e.g. Hatfield, Landers, & Ray, 1984). In contrast, poor shots have been associated with event-related desynchronization (e.g.…”
Section: Electroencephalography and Observationmentioning
confidence: 97%
“…These studies revealed changes in EEG activity with skill learning as well as differences in EEG power between novice and expert sport performers (Del Percio et al, 2008;Hatfield et al, 1984Hatfield et al, , 2004Haufler et al, 2000;Kerick et al, 2004;Landers et al, 1994;Slobounov et al, 2007). Specifically, the power computed for the alpha and theta frequency bands were positively related to the level of motor performance (Del Percio et al, 2008;Hatfield et al, 2004;Haufler et al, 2000;Kerick et al, 2004).…”
Section: Spectral Powermentioning
confidence: 99%
“…It is important to note that these biomarkers are able to detect important differences in skills level such as those existing between novices and experts (e.g., Hatfield et al, 1984Hatfield et al, , 2004Haufler et al, 2000) as well as to identify the learning dynamic related to different types of tasks inducing different neural resources (e.g., Gentili et al, 2008Gentili et al, , 2009aKerick et al, 2004). Moreover, although their scalp locations and frequency band of interest present slight variations from one task to another, it appears that these biomarkers share also some frequency (e.g., alpha band) and spatial (e.g., temporal region) features while being located on specific electrodes for the various tasks tested.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are clear to the player and bystanders like the "yips" in golf -focal dystonia [9], and others are hidden but none the less important for peak performance. The "relaxed but focused" state or zone has been the subject of much research [6,8] but this has mainly been conducted under laboratory conditions. There seems to be a strong correlation of alpha activity with the zone and it was clear that the Bristol Process with its advantages over the FFT would be very suitable for players on the move.…”
Section: Sports Medicinementioning
confidence: 99%